Moral Education in the View of Yunahar Ilyas - Sufri Situmorang, Jamaluddin; Akrim, Akrim; Harfiani, Rizka (International Journal of Social Science, Education, Communication and Economics, 2025)
This study examines the concept of moral education in the view of Yunahar Ilyas and its relevance in Indonesia. Moral education is an integral part of Islamic teachings, occupying a special and very important position, as evidenced by the many verses of the Qur'an and the hadith of the Prophet that discuss it. The concept of morality itself etymologically means character, temperament, behavior, or nature, which regulates human relations with God, others, and the universe. This study uses a qualitative method with a library research approach, collecting data from written materials such as books, journals, and articles, with the book "Kuliah Akhlaq" by Yunahar Ilyas as the primary data source. The results of the study show that Yunahar Ilyas places moral education as a fundamental foundation that does not grow by itself, but requires coaching, training, and hard work. This view is very relevant considering the degradation of morality in today's young generation, which requires educational institutions to conduct introspection and change in order to instill good moral and ethical values. Moral education, according to Yunahar Ilyas, is the foundation of true happiness in this world and the hereafter and is crucial to overcoming the moral crisis and forming a generation of integrity. This confirms the contribution of Yunahar Ilyas' thoughts in the context of moral education in Indonesia, which seeks to produce principles and truths according to the teachings of the Qur'an and as-sunnah.